Serum chromogranin A level continuously rises with the progression of type 1 diabetes, and indicates the presence of both enterochromaffin‐like cell hyperplasia and autoimmune gastritis - Zoltan Herold; Magdolna Herold; Peter Nagy; Attila Patocs; Marton Doleschall; Aniko Somogyi (Journal of Diabetes Investigation, 2020)
Abstract Aims/Introduction The relationship of chromogranin A (CgA) levels above the normal range with various outcomes, such as glycated hemoglobin levels, enterochromaffin‐like cell hyperplasia and autoimmune gastritis, was investigated in type 1 diabetes patients with special regard to the progression of comorbidities. Materials and Methods A cohort study on 153 type 1 diabetes patients was carried out with a prospective branch on clinical and laboratory data, and a retrospective branch on histological data obtained by gastroscopy. Results Patients with CgA levels above the upper limit of the normal range (n = 28) had significantly higher glycated hemoglobin levels (P = 0.0160) than those with CgA in the normal range (n = 125). The correlation between CgA and glycated hemoglobin was significant (P < 0.0001), but weak (R = +0.32). A slight, but steady elevation (P = 0.0410) in CgA level was observed to co‐vary with the duration of type 1 diabetes. Enterochromaffin‐like cell hyperplasia and autoimmune gastritis was significantly more frequent (P = 0.0087 for both) in the high CgA group. Detailed analyses on gastric tissue samples confirmed a progression of enterochromaffin‐like cell hyperplasia (P = 0.0192) accompanied by CgA elevation (P = 0.0316). Conclusions The early detection and follow up of the later progression of enterochromaffin‐like cell hyperplasia and autoimmune gastritis into gastric neuroendocrine tumors, which have ~100‐fold greater incidence in type 1 diabetes patients, can be achieved by assessment of CgA levels. Therefore, the use of CgA could be considered as a novel auxiliary biomarker in the care of these type 1 diabetes complications.